2021
DOI: 10.32098/mltj.04.2021.05
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Muscles and Tendons in Asymptomatic Individuals with Generalized Joint Hypermobility

Abstract: Background. The purpose of the present study was to investigate changes in mechanical properties of muscles and tendons in asymptomatic individuals with generalized joint hypermobility (GJH). Methods. This cross-sectional study was conducted in 126 participants aged 19-40 years. The Beighton score was used to determine whether the participants had GJH. An experienced physiotherapist screened all participants using the Beighton score to inquire about the presence of GJH. At the end of the clinical evaluations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(52 reference statements)
1
0
0
Order By: Relevance
“…Several previous studies measured the stiffness between the MG and the LG using the MyotonPRO and reported greater stiffness of the LG, similar to the present study, but none of the studies observed differences between the muscles, nor did they focus on the reason for the greater stiffness of the LG at rest [ 6 , 15 , 26 , 48 ]. There are very few architectural differences between the muscles.…”
Section: Discussionsupporting
confidence: 80%
“…Several previous studies measured the stiffness between the MG and the LG using the MyotonPRO and reported greater stiffness of the LG, similar to the present study, but none of the studies observed differences between the muscles, nor did they focus on the reason for the greater stiffness of the LG at rest [ 6 , 15 , 26 , 48 ]. There are very few architectural differences between the muscles.…”
Section: Discussionsupporting
confidence: 80%